The Association between Periodontal Disease on Pregnancy and the Incidence of Preterm Labor - Andoharman Damanik (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To determine the association between periodontal disease on pregnancy and the incidence of preterm labor. Method: This was a cross sectional study. We enrolled sixty subjects, which then divided into two groups. One group comparised of thirty pregnant women preterm delivery and thirty women with preterm pregnancy. Subjects were chosen by consecutive sampling method. The subject’s teeth except Molar III were evaluated for probing depth, bleeding on probing, calculus, and the results were interpreted according to CPITN (WHO,1997). Evaluation were conducted at Dental and Oral Health Clinic at Sanglah Hospital and Gianyar Hospital. Results: The subjects characteristic was not different between the two groups, hence its influence could be avoided. Using Chi-Square test, we found that periodontal disease on pregnant women was associated with preterm birth, with prevalence ratio of 2.30 (CI 95% 1.69-3.13, p=0.011). Conclusion: Diseases on pregnant mother is associated with the incidence of preterm labor. Periodontal diseases is found twice as many in women with preterm labor compared to pregnant woman who did not experienced any signs of preterm labor. [Indones J Obstet Gynecol 2012; 36-2: 85-9] Keywords: periodontal disease, preterm birth